Relative Resistance of Different Clones of Tectona grandis to Teak Defoliator, Hyblaea puera Cram (Lepidoptera : Hyblaeidae) in South India - Ahmad, Mukhtar (Indian Forester, 1987)
20 clones of teak, Tectona grandis belong to Kerala, Tamil Nadu and Andhra Pradesh were evaluated for their natural variation in susceptibility to teak defoliator, Hybiaea puera Cram (Lepidoptera: Hyblaeldae). Growth increment of the clones was also observed for a period of 17 months. TNT 6 was found to be the most resistant clone as the leaf area consumed by the larvae of H. Puera was 1.51 cm2. Whereas KLS 3 was the most susceptible (leaf area fed 17.78 cm2). Performance of clone KLK 2 was the best in respect of growth increment as it attained the maximum increment of 104.57 cdm, among the 20 clones observed. Intraspecific crosses are advised between clone TNT 6 aDd KLK 2 for further improvement of the c1one’s quality.